Investigating the Effectiveness of Educandy as Gamification in English Language Teaching to Improve Students' Vocabulary Mastery - Nur Ahista Balqist (Journal of Education, Linguistics, Literature and Language Teaching, 2024)
The purpose of this study was to investigate whether the Educandy application effect the students’ vocabulary mastery. The study focused on the seventh-grade students of SMP N 2 Langsa, with sample of 44 students, divided into an experimental class and a control class. A quantitave approach was employed, utilizing a quasi-experimental design. The research instrument consisted of a vocabulary test, and the data were gathered through pre-test and post-test. Analysis was conducted using non-parametric tests, specifically the Wilcoxon and Mann-Whitney tests. The findings indicated a significant improvement in the mean scores of the experimental class after using the Educandy application compared to the control class. Statistical analysis yielded an Asymp Sig. (2-tailed) value of 0.000. which is less than α = 0.05, leading to the rejection of H0 and acceptance of Ha. Therefore, the study concluded that Educandy application effectively enhances students’ vocabulary mastery.